Oral candidiasis in patients with liver cirrhosis: Kandidiasis oral pada pasien sirosis hati - Ali Taqwim; Vena Omi Hartini; Siti Mutia Ayuningtyas; Ni Ketut Donna Prisilia (Makassar Dental Journal PDGI Makassar, 2023)
Chronic hepatitis can lead to liver cirrhosis and hepatocellular carcinoma (HCC). Cirrhosis of the liver appears asymptoma-tic so it is not detected, including during dental treatment. Oral manifestations of cirrhosis of the liver include candidiasis, li-chen planus, ulcers, xerostomia, erosions, and tongue abnormalities. Immunosuppressant conditions in patients with liver cir-rhosis and the use of broad-spectrum antibiotics can cause oral candidiasis. A 69-year-old male who came with complaints of right abdominal pain, nausea, vomiting, weakness, and bloody bowel movements for 1 week. The patient complains of a sto-mach that is getting bigger and feels tight. The patient was diagnosed with cirrhosis liver and HCC. Oral manifestations in patients with liver cirrhosis include bacterial and fungal infections such as dental caries, periodontitis, and candidiasis. Oral candidiasis is inflammation of the oral mucosa caused by infection with the fungus Candida albicans which is an opportunistic microorganism. Drugs that can be given in first-line candidiasis conditions are nystatin, ampotesin B, and clotrimazole. It is concluded that one of the oral manifestations in liver cirrhosis was oral candidiasis due to immunosuppressant conditions.